Functional diversity between HSP70 paralogs caused by variable interactions with specific co-chaperones - Serlidaki, Despina; van Waarde, Maria A. W. H.; Rohland, Lukas; Wentink, Anne; Dekker, Suzanne L.; Kamphuis, Maarten J.; Boertien, Jeffrey M.; Brunsting, Jeanette F.; Nillegoda, Nadinath B.; Bukau, Bernd; Mayer, Matthias P.; Kampinga, Harm H.; et al. (The journal of biological chemistry, 2020)
Heat shock protein 70 (HSP70) chaperones play a central role in protein quality control and are crucial for many cellular processes, including protein folding, degradation, and disaggregation. Human HSP70s compose a family of 13 members that carry out their functions with the aid of even larger families of co-chaperones. A delicate interplay between HSP70s and co-chaperone recruitment is thought to determine substrate fate, yet it has been generally assumed that all Hsp70 paralogs have similar activities and are largely functionally redundant. However, here we found that when expressed in human cells, two highly homologous HSP70s, HSPA1A and HSPA1L, have opposing effects on cellular handling of various substrates. For example, HSPA1A reduced aggregation of the amyotrophic lateral sclerosis-associated protein variant superoxide dismutase 1 (SOD1)-A4V, whereas HSPA1L enhanced its aggregation. Intriguingly, variations in the substrate-binding domain of these HSP70s did not play a role in this difference. Instead, we observed that substrate fate is determined by differential interactions of the HSP70s with co-chaperones. Whereas most co-chaperones bound equally well to these two HSP70s, Hsp70/Hsp90-organizing protein (HOP) preferentially bound to HSPA1L, and the Hsp110 nucleotide-exchange factor HSPH2 preferred HSPA1A. The role of HSPH2 was especially crucial for the HSPA1A-mediated reduction in SOD1-A4V aggregation. These findings reveal a remarkable functional diversity at the level of the cellular HSP70s and indicate that this diversity is defined by their affinities for specific co-chaperones such as HSPH2.
Gesehen am 03.03.2021